Immunoglobulin free light chains and GAGs mediate Multiple Myeloma Extracellular Vesicles uptake and secondary NfkB nuclear translocation - Di Noto, Giuseppe; Chiarini, Marco; Paolini, Lucia; Mazzoldi, Elena; Giustini, Viviana; Radeghieri, Annalisa; Caimi, Luigi; Ricotta, Doris (Frontiers in Immunology, 2014)
Multiple Myeloma (MM) is a hematological malignancy caused by a microenviromentally-aided persistence of plasma cells in the bone marrow. Monoclonal plasma cells often secrete high amounts of immunoglobulin free light chains (FLCs) that could induce tissue damage. Recently we showed that FLCs are internalized in endothelial and myocardial cell lines and secreted in extracellular vesicles (EVs). MM serum derived EVs presented phenotypic differences if compared with Monoclonal gammophaty of undetermined significance (MGUS) serum derived EVs suggesting their involvement in MM pathogenesis or progression. To investigate the effect of circulating EVs on endothelial and myocardial cells we purified MM and MGUS serum derived EVs with differential ultracentrifugation protocols and tested their biological activity. We found that MM and MGUS EVs induced different proliferation and internalization rates in endothelial and myocardial cells, thus we tried to find specific targets in MM EVs docking and processing. Pre-treatment of EVs with anti FLCs antibodies or heparin blocked the MM EVs uptake highlighting that FLCs and Glycosaminoglycans (GAGs) are involved. Indeed only MM EVs exposure induced a strong NfkB nuclear translocation that was completely abolished after anti FLCs antibodies and heparin pre-treatment. The protein tyrosin kinase c-src is present on MM circulating EVs and redistributes to the cell plasma membrane after MM EVs exposure. The anti FLCs antibodies and heparin pre-treatment was able to block the intracellular redistribution of the c-src kinase and the subsequent c-src kinase containing EVs production. Our results open new insights in EVs cellular biology and in MM therapeutic and diagnostic approaches.